METHODOLOGICAL ASPECTS OF ASSESSING THE STEEL FRAMES RELIABILITY - Klymenko, Vasyl; Kravchenko, Volodymyr; Zotsenko, Mykola; Vynnykov, Yuriy; Martynenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2019)
The peculiarities of biogas technology application in the falling leaves utilization plants are analyzed and the application ofsoil cement is proposed to create the basic elements of such plants. A new schematic and constructive solution of biogasfermenter (bioreactor) with application of soil-cement technology with a blending method for efficient functioning oftechnological chain of biogas fermentation of fallen leaves and other plant residues for energy supply systems has beendeveloped. The possibility of reliable isolation of the space of the bioreactor to the excavation of the pit from the surroundingarray with soil cement screen is substantiated. The corrosion resistance of the soil cement waterproof screen has been proved.
Keywords: biogas plant for the disposal of fallen leaves; pit; soil cement; waterproofing; aggressive medium; strength; coefficient of chemical resistance; soil cement waterproof screen